Sex and the Origins of Death. - Clark, William R. (Oxford University Press, 1998)
Death, for bacteria, is not inevitable. Protect a bacterium from predators, and provide it with adequate food and space to grow, and it would continue living--and reproducing asexually--forever. But a paramecium (a slightly more advanced single-cell organism), under the same ideal conditions, would stop dividing after about 200 generations--and die. Death, for paramecia and their offspring, is inevitable. Unless they have sex ... € In Sex and the Origins of Death, William Clark ranges far and wide over fascinating terrain. Whether describing a 62-year-old man having a major heart attack (a.